Morphodynamics drive the transport and accumulation of anthropogenic microparticles in tropical coastal depositional systems in southeastern Brazil - Furlan, Isabela [UNESP]; Fornari, Milene [UNESP]; Sawakuchi, André Oliveira; Giannini, Paulo César Fonseca; Dipold, Jessica; de Freitas, Anderson Zanardi; Wetter, Niklaus Ursus; Semensatto, Décio (Elsevier, 2024)
A significant limitation in current coastal pollution research is that microplastics (<5 mm) comprise only a fraction of all anthropogenic microparticles (AMP, <5 mm) scale residues. Comprehensive AMP assessments, including those comprising semisynthetic, and modified natural compositions, are lacking. For instance, the accumulation of AMP in different coastal morphological features within a depositional system remains poorly known, fueling long-lasting debates about the distribution process of microparticles. Using a multi-proxy approach, we address mutual interactions between distinct surface morphologies (tidal flats, beaches, and foredunes) and transport and deposition dynamics of AMP. This issue was addressed by analyzing sediment and water samples collected at a marine protected area in the south coastal of São Paulo (Brazil). Here, we showed that AMP abundance in the tidal mudflat (18,500–20,500 particles/kg) was four times higher than in beach sands (4700–5900 particles/kg), while the lowest abundance was observed in foredune sands (4350 particles/kg). This can be attributed to the low-energy hydrodynamics of tidal flats associated with the cohesive behavior of muddy sediments, which consequently favor trapping and act as the main sink for AMP. Further, coastal processes (waves and currents) drive AMP onshore through sediment transport from the surfzone to the beach, from where the AMP becomes available for onshore eolian transport. Higher AMP abundance (85 particles/l) was observed in the marine water samples compared to the estuarine water samples (35 particles/l). Fibers <1 mm appeared as the predominant AMP in the sediment (99–100 %) and water (80–95 %) samples, primarily consisting of modified cellulose (73 %), dye signature only (16 %), and microplastics (11 %). Consequently, we argue that to fully comprehend the spatial distribution of AMP in coastal sediments and waters, it is crucial to analyze these microparticles from an integrated perspective, primarily considering the hydro-wind dynamics of different coastal morpho-sedimentary compartments combined with sediment grain size.